New hexactinellid sponges from deep Mediterranean canyons - Boury-Esnault, Nicole; Vacelet, Jean; Dubois, Maude; Goujard, Adrien; Fourt, Maïa; Pérez, Thierry; Chevaldonné, Pierre (Zootaxa, 2017)
During the exploration of the NW Mediterranean deep-sea canyons (MedSeaCan and CorSeaCan cruises), several hexactinellid sponges were observed and collected by ROV and manned submersible. Two of them appeared to be new species of Farrea and Tretodictyum. The genus Farrea had so far been reported with doubt from the Mediterranean and was listed as "taxa inquirenda" for two undescribed species. We here provide a proper description for the specimens encountered and sampled. The genus Tretodictyum had been recorded several times in the Mediterranean and in the near Atlantic as T. tubulosum Schulze, 1866, again with doubt, since the type locality is the Japan Sea. We here confirm that the Mediterranean specimens are a distinct new species which we describe. We also provide18S rDNA sequences of the two new species and include them in a phylogenetic tree of related hexactinellids.